Mechanobiology of Microvascular Function and Structure in Health and Disease: Focus on the Coronary Circulation - Brandt, Maarten M.; Cheng, Caroline; Merkus, Daphne; Duncker, Dirk J.; Sorop, Oana (Frontiers in Physiology, 2021)
The coronary microvasculature plays a key role in regulating the tight coupling between myocardial perfusion and myocardial oxygen demand across a wide range of cardiac activity. Short term regulation of coronary blood flow in response to metabolic stimuli, is achieved via adjustment of vascular diameter in different segments of the microvasculature in conjunction with mechanical forces eliciting myogenic and flow-mediated vasodilation. In contrast, chronic adjustments in flow regulation also involve structural modifications of the microvasculature, termed remodeling. Vascular remodeling encompasses changes in microvascular diameter and/or density and is largely modulated by mechanical forces acting on the endothelium and vascular smooth muscle cells. Whereas in recent years, substantial knowledge has been gathered regarding the molecular mechanisms controlling microvascular tone and how these are altered in various diseases, the structural adaptations in response to pathologic situations are less well understood. In this article we will review the factors involved in coronary microvascular functional and structural alterations in obstructive and non-obstructive coronary artery disease and the molecular mechanisms involved herein with a focus on mechanobiology. Cardiovascular risk factors including metabolic dysregulation, hypercholesterolemia, hypertension and aging have been shown to induce microvascular (endothelial) dysfunction and vascular remodeling. Additionally, alterations in biomechanical forces produced by a coronary artery stenosis are associated with microvascular functional and structural alterations. Future studies should be directed at further unraveling the mechanisms underlying the coronary microvascular functional and structural alterations in coronary artery disease. A deeper understanding of these mechanisms is critical for the identification of potential new targets for the treatment of ischemic heart disease.